Diagnostic test of mammography in a palpable mass of the breast - Rosalia Sri Sulistijawati Henry Kusumo Husodoputro Bambang Udji Djoko Rianto (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2008)
Background: Breast cancer is the most common cancer in Indonesia after cervical cancer. The diagnosis of breast cancer is based on triple diagnostics, clinical diagnostic, mammograph, and fine needle aspiration biopsy (FNAB). Mammograph is a non-invasive radiologic imaging to demonstrate microcalcification as an early sign of breast cancer.Objective: The aim of this study was to measure the validity of mammograph in a palpable mass of the breast.Methods: Study design for this study was a diagnostic test that compared mammograph with histopatology result as the gold standard. Study was performed between March 2006 and September 2007 in Sardjito General Hospital, Yogyakarta. There were 79 palpable masses of the breast that were included as the subjects of this study. They were mammographed and examined histopatologically. Descriptive analysis with McNemar non parametric test with 2x2 table was performed by a computer software program to calculate sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), positivelikelihood ratio (positive LR) and negative likelihood ratio (negative LR). .Results: Sensitivity, specificity, PPV, NPV, positive LR and negative LR of mammograph in diagnosing a breast palpable mass were 87.18%,87.50%,87.18%,87,50%,7, and 0.146, respectively Conclusion: Mammograph had a high validity in diagnosing breast palpable masses.Key words: breast palpable mass - mammograph - diagnostic test - validity.